Unlocking the potential of CO2 hydrogenation into valuable products using noble metal catalysts: A comprehensive review - Muhammad Tawalbeh (15901018) (2023)
The research towards the development of alternative fuel generation technologies has been triggered by Climate change, global warming, and the ongoing depletion of fossil fuels. The hydrogenation of carbon dioxide (CO2) into methanol, dimethyl ether, carbon monoxide, and value-added products appears to be a promising path to mitigate CO2 emissions. The role of noble metal catalysts (Pt, Pd, Rh, Au, etc.) in CO2 conversion into useful products has been addressed in this work. The literature reported improved catalytic performance of the reverse water-gas shift (RWGS) reaction, and several studies were examined for the optimal performance in CO2 hydrogenation processes. The focus was on the preparation techniques, supporting materials, noble metals loading, and reactions mechanism. This paper shows the most notable results in the application of noble metals and demonstrates an enhanced CO2 conversion of 80% and CO selectivity of >99%. Furthermore, this review demonstrated the promising role of Au-based catalysts in improving the kinetics of the CO2 hydrogenation reaction with 80% methanol selectivity when nano-sized zinc oxide particles were involved. Recently, CO2 hydrogenation with photothermal catalysis resulted in a high methane yield and selectivity of 100%. Notable research paths were directed toward the investigation of Au and Pd-based catalysts and exploited them to produce formats compounds with promising conversion. Furthermore, the synthesis of heterogeneous oxide-zeolite (OX-ZEO) bi-functional catalysts for improved CO2 hydrogenation can be explored in reactors powered by renewable energy sources. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.eti.2023.103217